Security, obedience, and the emergence of violence in contexts of confinement - Perlo, Claudia Liliana; Carmona Gallego, Diego; Carlín, María Celeste (Revista Colombiana de Ciencias Sociales, 2025)
In this article, we further develop theoretical reflections on the relationship between obedience and violence within the contemporary security paradigm in contexts of confinement. These reflections stem from the conceptual and theoretical framework that informs our research, framed within confinement as a socio-educational setting. We understand violence as a complex social phenomenon tied to a socio-historical trajectory generated by patriarchal living conditions that have fragmented the human experience. We begin by examining the repressive-punitive paradigm that underpins current public policies anchored in security, with special emphasis on penitentiary policies. We then delve into the theoretical contributions surrounding the banality of evil, revisiting the landmark experiments conducted by social psychologists Stanley Milgram (1963) and Philip Zimbardo (1969), which empirically support the thesis advanced by philosopher Hannah Arendt (1963/1999). These contributions lead us to review recent epigenetic research on the contextual factors that foster violence. Our methodology—guided by participatory action research—allows the articulation of vivid field testimonies with the theoretical developments presented here. Finally, we propose conclusions regarding the tensions between security and care within confinement, tensions that ultimately place contemporary democracies in a precarious position.